从吸引到融入：新加坡1990年代到2010年代移民政策的趋势 = From attracting to integrating : Singapore’s immigration policy trend from the 1990s to 2010s - 谢璧禧 Chia, Michelle Peck Hee (2013)
新加坡作为一个移民社会，移民200 年间不断的涌入，但近年来关于移民的问题在新加坡社会里越来越受关注。本文基于新加坡的移民历史，研究新加坡政府的移民政策从90 年代以来的趋势，从吸引外来人才的“联络新加坡”到融入新移民的“新加坡融合理事会”，并针对已经成为新加坡公民的中国新移民，看宗乡会馆、新移民团体“华源会”和以华语为媒介的媒体，如何制造一个大环境，以国家建设的方式帮助中国新移民融入。而依据本尼迪克特 • 安德森“想象的共同体”的说法，新加坡在试图建构单一的“想象共同体”的过程中，看似也产生了新加坡人和新移民之间更深的隔阂。As an immigrant society, Singapore has constantly been receiving immigrants for the past 200 years.However, issues regarding the new immigrants have become a rising concern in the Singapore society. This paper bases itself on Singapore’s immigrant history, and observes Singapore’s immigration policy trend that has shifted its focus from attracting foreign talents in the 1990s, as seen from “Contact Singapore” as the organization to have executed this policy, to integrating new immigrants in the 2010s, in which the “National Integration Council” was set up. Focus is placed specifically on the Chinese immigrants, as the paper looks at how grassroots organisations, clan associations and Hua Yuan General Association of New Immigrants from China, and Singapore’s Chinese language media are actively involved in integrating new immigrants through the nation-building approach. According to Benedict Anderson’s concept of “Imagined Communities”, in an attempt to construct one imagined community within the nation, Singapore’s efforts seemed to also further set apart Singapore citizens and her new citizens.